Death as Surprise in 18th and 19th Centuries Romanticism - Simut, Ramona (Richtmann Publishing, 2012)
One of the major themes of discussion in the art and especially the literature of the 18th and 19th centuries was the problem ofdeath. In the beginning this seemed to be the case mostly because of the natural processes related to death as a transforming event ofthe human body and mind. However, towards the end of the 18th century and well into the 19 century, a certain shift took place from thecommon and normal perspective on death to a rather accessorized and scientific literary approach. Our attempt is to notice and makethe necessary connections between the concepts of nature (both the human nature and the external-physical nature) and the innovativetechnologies recently implemented in the society of the time, with reference to the new accidental and commercial facets of death asdestruction of nature especially in the work of the American Romantics R. W. Emerson and H. D. Thoreau. Aware that they are highlyspoken of in view of their transcendentalism as a particular philosophy about the bond between man and nature, we will slowly come toterms with this type of concerns and connect them to the conflicting reality of the industrialization as a sudden and repressivephenomenon within the society of men. Finally our point is that precisely this phenomenon caused these writers to make a historicaldetour and use their naturalist formation in order to make sense of their century deaths and diseases.